2005
DOI: 10.1093/hmg/ddi121
|View full text |Cite
|
Sign up to set email alerts
|

GDAP1, the protein causing Charcot–Marie–Tooth disease type 4A, is expressed in neurons and is associated with mitochondria

Abstract: Mutations in GDAP1, the ganglioside-induced differentiation-associated protein 1 gene, cause Charcot-Marie-Tooth (CMT) type 4A, a severe autosomal recessive form of neuropathy associated with either demyelinating or axonal phenotypes. Here, we demonstrate that GDAP1 has far greater expression in neurons than in myelinating Schwann cells. We investigated cell localization of GDAP1 in a human neuroblastoma cell line by means of transient overexpression and co-localization with organelle markers in COS-7 cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 26 publications
7
137
1
5
Order By: Relevance
“…1). Besides FIS1 in mammals [30], MTP18 [31], endophilin B1 [32] and GDAP1 [33], other new players have also been recently identified, such as MFF, MiD49, and MiD51 (or MIeF1), all required for cytoplasmatically-localized DRP1 activation and for its recruitment to mitochondria fission sites [34,35]. It has been shown that MiD49/MiD51 also recruit DRP1 to the mitochondria in the absence of hFIS1 and/or MFF [36].…”
Section: Inf2mentioning
confidence: 99%
“…1). Besides FIS1 in mammals [30], MTP18 [31], endophilin B1 [32] and GDAP1 [33], other new players have also been recently identified, such as MFF, MiD49, and MiD51 (or MIeF1), all required for cytoplasmatically-localized DRP1 activation and for its recruitment to mitochondria fission sites [34,35]. It has been shown that MiD49/MiD51 also recruit DRP1 to the mitochondria in the absence of hFIS1 and/or MFF [36].…”
Section: Inf2mentioning
confidence: 99%
“…Another protein, Mtp-18, induces Drp-1-dependent mitochondrial fission (Tondera et al, 2004(Tondera et al, , 2005. Finally, over-expression of Gdap-1, a protein of the MOM, induces mitochondrial fission, whereas its loss of function induces mitochondrial elongation (Niemann et al, 2005;Pedrola et al, 2005).…”
Section: Mitochondrial Fissionmentioning
confidence: 99%
“…A large subset of patients with CMT type 2A (CMT2A) were found to have a mutations in the mitofusin 2 (MFN2) gene, primarily localized to the GTPase domain, 70 and typically exhibit earlier onset and increased severity compared with CMT2 patients without MFN2 mutations. 71 In addition, several mutations leading to the CMT type 4A disease phenotype were traced to the ganglioside-induced differentiation-associated protein 1 (GDAP1) gene, 72 a regulator of mitochondrial fission. 73 Although the precise cellular physiologic mechanism(s) underlying the disease pathology is still poorly understood, disease-associated mutations in MFN2 and GDAP1 lead to abnormal formation of mitochondrial networks in peripheral nerve axons and myelin sheaths.…”
Section: Neural Disease: a Role For Mitochondrial Turnover And Dynamicsmentioning
confidence: 99%